Understanding Community Appropriate Metadata through Bernstein's Theory of Language Codes. Issue 1 (2nd January 2017) - Farnel, Sharon
ABSTRACT: Digital libraries are developed by and for their communities. Metadata is a key aspect of digital libraries, and so it too must reflect the contexts of those communities. In this paper I argue that Basil Bernstein's theory of language codes as socially constructed phenomena that reflect the contexts of the communities in which they are used provides novel methods for approaching the notion of community appropriate metadata. It reminds us that metadata is socially constructed; encourages us to look at metadata holistically; offers a means of understanding community appropriate metadata as instances of restricted codes; and provides an intriguing method for analyzing traditional metadata structures such as large, comprehensive controlled vocabularies and classification systems.